Isoindigo-based polymer field-effect transistors: effects of selenophene-substitution on high charge carrier mobility1. Issue 38 (11th May 2015) - Park, Kwang Hun; Cheon, Kwang Hee; Lee, Yun-Ji; Chung, Dae Sung; Kwon, Soon-Ki; Kim, Yun-Hi
<x xml:space="preserve">Abstract</x> The selenophene-substitution can lead to a higher crystalline order as well as a high charge carrier mobility in isoindigo-based polymers.